Training Legal Skills in the ESP Classroom: Mediation Activities and Student Self-Reflection - Chovancova, Barbora (HERMES - Journal of Language and Communication in Business, 2024)
A general trend in adult education across the disciplines has been the gradual shift from teaching specialized knowledge to developing various skills. The inclusion of professional skills in the area of Languages for Specific Purposes (LSP) is often based on the results of complex needs analyses of the target situation that leads to effective course design both for in-service and pre-service learners. While major law schools have recently started putting a greater emphasis on the training of legal skills, the present article suggests that some of those legal skills can be effectively developed in the ELP (English for Legal Purposes) classroom as well, i.e. among L2 learners of specialist language. That holds particularly for the soft skill of linguistic mediation. Promoted by CEFR, mediation is characterized by the situation when an expert speaker needs to overcome a communicative gap arising from a difference in the technical or linguistic knowledge of the interlocutors. The present article shows how a sample activity can be used for teaching linguistic mediation in the ELP classroom and how it can serve as an opportunity for enhancing students’ critical self-reflection. It describes a custom-made activity – a role-played lawyer-client interview – and analyses students’ subsequent comments on the activity. The paper suggests that self-reflection is deeper if the theory is supplied after the task and that such a practice enhances students’ learning process. It is suggested that the findings are applicable not only to teachers’ syllabus design and classroom activities design but also more generally to pedagogic theory, e.g. the field of LSP teacher training.